2018
DOI: 10.1007/s10103-018-2638-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photobiomodulation on neural differentiation of human umbilical cord mesenchymal stem cells

Abstract: Photobiomodulation therapy (PBMT) can enhance the mesenchymal stem cell (MSC) proliferation, differentiation, and tissue repair and can therefore be used in regenerative medicine. The objective of this study is to investigate the effects of photobiomodulation on the directional neural differentiation of human umbilical cord mesenchymal stem cells (hUC-MSCs) and provide a theoretical basis for neurogenesis. hUC-MSCs were divided into control, inducer, laser, and lasers combined with inducer groups. A 635-nm las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…In order to investigate mitochondrial activity in the MSCs, it has been shown that the intensity mean of rhodamin123 fluorescence increases significantly compared to the laser-free MSCs. 23,25 Angiogenic properties increase significantly in the underlying laser MSCs by increasing the expression of angiogenesis-related genes (VEGF, PDGF, HGF, BFGF, ANGPT1, ANGPT2, SDF-a1), which can damage endothelial cells and can significantly increase total tube length and branch point compared to the laser-free MSCs. The study showed that low-level laser irradiation could increase angiogenesis by the inhibition of apoptosis in the mesenchymal stem.…”
Section: The Variety Of Mesenchymal Stem Cells Umbilical Cord-mesenchmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate mitochondrial activity in the MSCs, it has been shown that the intensity mean of rhodamin123 fluorescence increases significantly compared to the laser-free MSCs. 23,25 Angiogenic properties increase significantly in the underlying laser MSCs by increasing the expression of angiogenesis-related genes (VEGF, PDGF, HGF, BFGF, ANGPT1, ANGPT2, SDF-a1), which can damage endothelial cells and can significantly increase total tube length and branch point compared to the laser-free MSCs. The study showed that low-level laser irradiation could increase angiogenesis by the inhibition of apoptosis in the mesenchymal stem.…”
Section: The Variety Of Mesenchymal Stem Cells Umbilical Cord-mesenchmentioning
confidence: 99%
“…The study also found that only an 808 nm laser could express the NeuN marker protein of neurons in 72 hours and a 635 nm laser increased the proliferation of the mesenchymal cells. 25 A laser with a wavelength of 635nm amplified the umbilical cord mesenchymal cells if it proved that a low-power laser with 808nm failed to increase the proliferation of the same cells. 26 Adipose Mesenchymal Stem Cells It has been reported that the toxic effects of doxorubicin on the adipose mesenchymal stem cells can be reduced by using a low-power laser with a wavelength of 660 nm, output power of 30 mW, a laser beam of 0.028 cm 2 , and irradiation of 1.07 mW/cm 2 .…”
Section: The Variety Of Mesenchymal Stem Cells Umbilical Cord-mesenchmentioning
confidence: 99%
“…Because of the continuous laser treatment, combined therapy can reduce the influence of adverse factors, including inflammation and edema. Furthermore, in previous studies, it was shown that laser irradiation significantly improved the activity of stem cells and improve the viability of cells (H. Chen et al, 2019), and that surviving hUCMSCs secreted neurotrophic factors and improved the microenvironment, thereby indicating the effect of combined therapy is obvious.…”
Section: Discussionmentioning
confidence: 93%
“…The hUCMSCs were provided by Tianjin Angsai Cell Genetic Engineering Co. Ltd., and were cultured and identified as described previously (H. Chen et al, 2019). Briefly, the cells were seeded in α‐MEN containing 10% fetal bovine serum, 0.05 U/ml penicillin and 0.05 μg/ml streptomycin, and cultured at 37°C under 5% CO 2 till the cells were 80–90% confluent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation